Dampak Stereotip pada Alumni Pondok Pesantren Islam Al Mukmin Ngruki terhadap Isu-isu Terorisme - Fadlilah Hanifah; Joko Subando; M Fatchurrohman (Pawarta: Journal of Communication and Da'wah, 2023)
The purpose of this study is to discuss how stereotypes received by alumni of Pondok Pesantren Al Mukmin Ngruki who were once suspected of being terrorists and find out how the impact received by alumni as former terrorist suspects. This study uses a descriptive qualitative method and a phenomenological-naturalistic approach. The research design used a multisite study conducted at the Pondok Pesantren Al Mukmin Ngruki with alumni and the community around. Data collection was carried out by interview, observation, and documentation methods. Data analysis used individual-site analysis and cross-site analysis techniques. To test the validity of the data is done through credibility, transferability, dependability, and confirmability. The results of this study indicate that the form of community stereotypes obtained by alumni of Pondok Pesantren Al Mukmin Ngruki who were suspected of being terrorists, includes two things namely positive stereotypes and negative stereotypes. From the statements of sources, both ES and MN provided information that the stereotypes they faced were not too prominent. While the stereotypes they get from the community are more positive stereotypes than negative stereotypes. This certainly has an impact on several subjects related to widespread stigma or stereotypes in society. Of course this is a common concern, as social beings who have their rights. You shouldn't always be judged just because you were accused or even when proven guilty.